PENGARUH PEMBIAYAAN MUDHARABAH, MUSYARAKAH DAN NON PERFORMING FINANCING TERHADAP PROFITABILITAS BANK PEMBIAYAAN RAKYAT SYARIAH DI PROVINSI JAWA BARAT PERIODE 2017-2020 - Wina Aprilia; Nana Diana (Jurnal Ilmiah Akuntansi Indonesia, 2021)
The purpose of this research is to determine influence mudharabah financing (X1), musyarakah financing (X2) and non performing financing (X3) on profitability (ROA) (Y) at Bank Pembiayaan Rakyat Syariah (BPRS) in West Java for the 2017 – September 2020 period. The population in this study were all Bank Pembiayaan Rakyat Syariah (BPRS) in West Java reistered with Otoritas Jasa Keuangan (OJK) for the 2017 – September 2020 period. The sample of this research is 3 BPRS from 28 population using purposive sampling method. The analytical method used is Multiple Linear Regression. The results of this research indicate that partially mudharabah and musyarakah have not effect on profitability (ROA), while non performing financing (NPF) variables has a negative and significant effect on profitability (ROA). Simultaneously there is an influence between mudharabah, musyarakah and non performing financing on profitability (ROA) together.